SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN PANGAN NON TUNAI (BPNT) DENGAN METODE ADDITIVE RATIO ASSESSMENT (ARAS) Studi Kasus: Desa Muncan - Baiq Dea Zualina; Wafiah Murniati; Asri Zaen, Mohammad Taufan (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2022)
BPNT is non-cash food aid. What is paid in the form of food by the government. The BPNT program aims to provide opportunities for the government to improve food security and provide balanced nutritional value to poor families, such as in Muncan Village, the BPNT assistance program is distributed every month. In decision-making, the selection of BPNT recipients is constrained because quite a lot of data that is processed or selected by the apparatus is still done manually. So far, the existing system has not been optimal for selecting BPNT recipients with the existing criteria. Data management still uses a manual system and is not effective in determining who is entitled to receive BPNT and who is not. The method used in the decision support system for Social Assistance for Non-cash Food Assistance (BPNT) is the ARAS method to make it easier to identify who is eligible to receive and who is not. support Based on the weight value obtained in the assessment process. The criteria for determining BPNT assistance include: occupation, number of dependents, income, home ownership, electric power and age. For testing using the Black Box method using the Boundary Value technique focusing on errors. The programming language used is PHP or Hypertext Preprocessor.